Application of an updated methodology to estimate the burden of healthcare-associated infections in Italy, 2022 - Italian PPS network (Eurosurveillance)
Background Accurate burden estimates are necessary to inform priority setting and rational resource allocation. Weighting prevalence inversely proportional to time-at-risk has been proposed as a solution for length-biased sampling, an important limitation affecting prevalence to incidence conversion for healthcare-associated infections (HAIs). Aim This study aimed to update Italian burden estimates by calculating HAI incidence, attributable mortality and disability-adjusted life years (DALYs). Further, we describe an adapted methodology for burden estimations. Methods We used data from the latest European Centre for Disease Prevention and Control (ECDC) point prevalence survey (PPS) of HAIs, conducted in Italy in November 2022, to calculate the burden of five major HAIs at national level. We adapted the Burden of Communicable Diseases in Europe (BCoDE) methodology to include inverse probability weighting and compared results of naïve and weighted calculations. Results The national sample included 18,397 patients. Overall, 564.8 DALYs per 100,000 general population resulted from weighted calculations (95% uncertainty interval (UI): 450.04–694.38), with an annual incidence of 685.42 cases per 100,000 general population (95% UI: 611.09–760.86) and 33.23 deaths per 100,000 general population per year (95% UI: 28.62–38.33). Concerning naïve estimates, overall 1,017.81 DALYs per 100,000 general population were calculated (95% UI: 855.16–1,190.59). In both calculations, healthcare-acquired bloodstream infections had the highest burden in terms of DALYs per 100,000 hospitalised and general population. Conclusion Our study confirmed the substantial burden of HAIs in Italy and renews the need to prioritise resources for infection prevention and control interventions.